Management of Adult Primary Immune Thrombocytopenia: Delphi-Based Consensus Recommendations - TOPTAŞ, TAYFUR (My University, 2024)
Objective: Primary immune thrombocytopenia (pITP) is an acquired autoimmune disorder related to the increased destruction and/or impaired production of platelets. Its diagnosis and management are challenging and require expertise and the interpretation of international consensus reports and guidelines with national variations in availability. We aimed to assess the agreement of hematologists in Türkiye on certain aspects of both first-line and second-line management of patients with pITP. Materials and Methods: Applying a modified Delphi method, the Turkish National ITP Working Group (14 steering committee members), founded under the auspices of the Turkish Society of Hematology, developed a 21-item questionnaire consisting of statements regarding the first-line and second-line treatment of pITP. A total of 107 adult hematologists working in either university or state hospitals voted for their agreement or disagreement with the statements in two consecutive rounds. Results: The participants reached consensus on the use of corticosteroids as first-line treatment and with limited duration. Methylprednisolone was the corticosteroid of choice rather than dexamethasone. Use of intravenous immunoglobulin was not preferred for patients without bleeding. It was also agreed that thrombopoietin receptor antagonists (TPO-RAs) or rituximab should be recommended as second-line treatment and that splenectomy could be considered 12-24 months after diagnosis in patients with chronic pITP. Conclusion: The optimization of the dose and duration of TPO-RAs in addition to corticosteroids is necessary to improve the management of patients with pITP. Keywords: Adult primary immune thrombocytopenia, Management, Delphi method

Amaç: Primer immün trombositopeni (pITP), trombositlerin artan yıkımı ve/veya bozulmuş üretimi ile ilişkili edinsel bir oto-immün hastalıktır. pITP’nin tanı ve yönetimi zorludur; ayrıca hem uzmanlık hem de uluslararası fikir birliği raporları ile kılavuzlarının, ulusal farklılıkları da göz önünde bulundurarak, yorumlanmasını gerektirir. Bu çalışmada Türkiye’deki hematologların pITP hastalarının birinci ve ikinci basamak tedavisinin belirli alanlarındaki fikir birliği düzeylerini değerlendirmeyi amaçladık. Gereç ve Yöntemler: Türk Hematoloji Derneği bünyesinde kurulan Türkiye Ulusal ITP Çalışma Grubu (14 yürütme kurulu üyesi), modifiye Delphi yöntemi ile pITP’nin birinci basamak ve sonraki tedavilerine ilişkin ifadelerden oluşan 21 maddelik bir anket geliştirdi. Üniversite veya devlet hastanelerinde çalışan 107 yetişkin hematolog, ardışık iki tur boyunca ifadelere katılıp katılmama yönünde oy kullandı. Bulgular: Katılımcılar kortikosteroidlerin birinci basamak tedavi olarak ve sınırlı süreyle kullanılması konusunda fikir birliğine vardı. Metilprednizolonun, dekzametazondan ziyade tercih edilen kortikosteroid olduğu gözlendi. İntravenöz immünoglobulin tedavisinin kanama dışında kullanımı tercih edilmez iken, thrombopoietin reseptör antagonistleri (TPO-RA) veya rituksimab ikinci basamak tedavi olarak önerilebileceği, kronik pITP hastalarında tanıdan 12-24 ay sonra splenektomi düşünülebileceği konusunda da görüş birliğine varıldı. Sonuç: pITP’li hastaların yönetimini iyileştirmek için kortikosteroidlerin yanı sıra TPO-RA’ların doz ve süresinin optimizasyonu gerekli olduğu konusunda fikir birliği sağlanmıştır. Anahtar Sözcükler: Erişkin primer immün trombositopeni, Hastalık yönetimi, Delphi metodu
Erişkin Primer İmmün Trombositopeni Yönetimi: Delphi-Temelli Uzlaşı Önerileri
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEMATOLOGY; Adult primary immune thrombocytopenia; Delphi method; Management; Erişkin primer immün trombositopeni; Hastalık yönetimi; Delphi metodu; Adult primary immune thrombocytopenia; Management; Delphi method